2005
DOI: 10.1136/bmj.331.7517.590
|View full text |Cite
|
Sign up to set email alerts
|

Soft tissue tumours of the extremities

Abstract: Require a high index of suspicion to enable early referral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 3 publications
1
20
0
Order By: Relevance
“…However, only one case of soft tissue sarcoma would be expected in this population every 24 years. 17 It is well-recognised, however, that soft tissue sarcomas present late with the average size of presentation of a deep extremity sarcoma being 8 cm and that of a superficial sarcoma being 3 cm. 5,18 The reason for late presentation is not entirely understood but is partly because many of these sarcomas will have no symptoms other than the presence of a painless mass.…”
Section: Discussionmentioning
confidence: 99%
“…However, only one case of soft tissue sarcoma would be expected in this population every 24 years. 17 It is well-recognised, however, that soft tissue sarcomas present late with the average size of presentation of a deep extremity sarcoma being 8 cm and that of a superficial sarcoma being 3 cm. 5,18 The reason for late presentation is not entirely understood but is partly because many of these sarcomas will have no symptoms other than the presence of a painless mass.…”
Section: Discussionmentioning
confidence: 99%
“…The literature has reported that a general physician may see one STS case in 24 years [2]. Meticulous workup in terms of radiological and histopathological evaluation is required for diagnosis and planning a multidisciplinary treatment strategy.…”
Section: Introductionmentioning
confidence: 99%
“…However, because soft tissue sarcomas (STSs) are rare—on average a family doctor will see just one case for every 24 years of practice [8]—malignancy is not always suspected, with the consequence that referral is delayed, or the patient is treated in a nonspecialist centre.…”
Section: Discussionmentioning
confidence: 99%